2020
DOI: 10.3390/cells9051295
|View full text |Cite
|
Sign up to set email alerts
|

Dual Independent Roles of the p24 Complex in Selectivity of Secretory Cargo Export from the Endoplasmic Reticulum

Abstract: The cellular mechanisms that ensure the selectivity and fidelity of secretory cargo protein transport from the endoplasmic reticulum (ER) to the Golgi are still not well understood. The p24 protein complex acts as a specific cargo receptor for GPI-anchored proteins by facilitating their ER exit through a specialized export pathway in yeast. In parallel, the p24 complex can also exit the ER using the general pathway that exports the rest of secretory proteins with their respective cargo receptors. Here, we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…MPPE1 encodes PGAP5, a widely expressed metalloproteinase 19 integral to the GPI biosynthesis and protein‐anchoring pathway, a highly conserved eukaryotic posttranslational modification 10 . The addition and modification of a GPI anchor is essential for the trafficking of certain proteins from the ER to the Golgi and cell surface 20,21 . The MPPE1 variant p.Arg329* likely leads to translation of a truncated protein lacking the KxKxx ER retrieval signal, which is crucial for correct PGAP5 localization 7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MPPE1 encodes PGAP5, a widely expressed metalloproteinase 19 integral to the GPI biosynthesis and protein‐anchoring pathway, a highly conserved eukaryotic posttranslational modification 10 . The addition and modification of a GPI anchor is essential for the trafficking of certain proteins from the ER to the Golgi and cell surface 20,21 . The MPPE1 variant p.Arg329* likely leads to translation of a truncated protein lacking the KxKxx ER retrieval signal, which is crucial for correct PGAP5 localization 7 .…”
Section: Discussionmentioning
confidence: 99%
“…10 The addition and modification of a GPI anchor is essential for the trafficking of certain proteins from the ER to the Golgi and cell surface. 20,21 The MPPE1 variant FIG. 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, along with reports of defects in the transport of specific cargos, evidence of more general impairments upon p24 deficiencies exist in the literature as well, such as altered Golgi-ER retrograde transport (Aguilera-Romero et al, 2008; Gommel et al, 2001; Majoul et al, 1998; Montesinos et al, 2014) and abnormal Golgi morphology (D’Arcangelo et al, 2015; Denzel et al, 2000; Koegler et al, 2010; Lavoie et al, 1999; Mitrovic et al, 2008; Pastor-Cantizano et al, 2018; Rojo et al, 2000). Moreover, broad roles have been ascribed to p24 proteins in mediating ER retention for quality control (Belden and Barlowe, 2001; Dvela-Levitt et al, 2019; Gomez-Navarro et al, 2020; Lopez et al, 2020; Ma et al, 2017; Springer et al, 2000; Wen and Greenwald, 1999), membrane contact during autophagosome formation from the ERGIC (ER Golgi Intermediate Compartment) (Li et al, 2022) and lipid transfer between the ER and Golgi (Anwar et al, 2022). Fitting all these proposed functions, cargo-specific and general, into a consistent view is problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this luminal topology, newly synthesized GPI-APs require a transmembrane cargo receptor that connects them with the cytosolic COPII coat for ER export. Previous studies from our laboratory and others suggested that the p24 protein complex, composed of type I transmembrane p24 proteins, can act as a specific cargo receptor for GPI-APs [7][8][9]. It was hypothesized that the p24 receptor would link GPI-APs to Lst1, a specialized isoform of the major COPII coat cargo binding subunit Sec24, to be actively packaged into nascent COPII vesicles [5,7,10].…”
Section: Introductionmentioning
confidence: 99%